ER-Localized PIN Carriers: Regulators of Intracellular Auxin Homeostasis - Abdollahi Sisi, Nayyer; Růžička, Kamil (Plants (Basel, Switzerland), 2020)
The proper distribution of the hormone auxin is essential for plant development. It is channeled by auxin efflux carriers of the PIN family, typically asymmetrically located on the plasma membrane (PM). Several studies demonstrated that some PIN transporters are also located at the endoplasmic reticulum (ER). From the PM-PINs, they differ in a shorter internal hydrophilic loop, which carries the most important structural features required for their subcellular localization, but their biological role is otherwise relatively poorly known. We discuss how ER-PINs take part in maintaining intracellular auxin homeostasis, possibly by modulating the internal levels of IAA; it seems that the exact identity of the metabolites downstream of ER-PINs is not entirely clear as well. We further review the current knowledge about their predicted structure, evolution and localization. Finally, we also summarize their role in plant development.
Keywords: auxin metabolism; ER-PINs; PIN proteins; auxin transport; PIN5; PIN8